Pacific literatures as world literature - Lin, Chia-hua (Chia-hua Yvonne); Huang, Hsinya (Literatures as world literature., 2023)
Pacific Literatures as World Literature is a conjuration of trans-Pacific poets and writers whose work enacts forces of “becoming oceanic” and suggests a different mode of understanding, viewing, and belonging to the world. The Pacific, past and present, remains uneasily amenable to territorial demarcations of national or marine sovereignty. At the same time, as a planetary element necessary to sustaining life and well-being, the Pacific could become the means to envisioning ecological solidarity, if compellingly framed in terms that elicit consent and inspire an imagination of co-belonging and care. The Pacific can signify a bioregional site of coalitional promise as much as a danger zone of antagonistic peril.